2021
DOI: 10.7717/peerj.11182
|View full text |Cite
|
Sign up to set email alerts
|

The classification of EEG-based winking signals: a transfer learning and random forest pipeline

Abstract: Brain Computer-Interface (BCI) technology plays a considerable role in the control of rehabilitation or peripheral devices for stroke patients. This is particularly due to their inability to control such devices from their inherent physical limitations after such an attack. More often than not, the control of such devices exploits electroencephalogram (EEG) signals. Nonetheless, it is worth noting that the extraction of the features and the classification of the signals is non-trivial for a successful BCI syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…The present study has demonstrated that through the proposed pipeline, a better classification accuracy could be achieved as compared to the conventional means reported in the literature, particularly with regards to the classification of skateboarding tricks. The encouraging results reported suggests that the proposed pipeline could be beneficial in providing an objective-based judgment in The findings of the present investigation are in agreement with other studies that have employed such a technique in different applications, for instance, Lee, Yoon and Cho (2017) , Rangasamy et al (2020) as well as Mahendra Kumar et al (2021) . Nonetheless, it is worth noting that the efficacy of the pipelines is highly dependent on the dataset utilized, and the performance may vary.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The present study has demonstrated that through the proposed pipeline, a better classification accuracy could be achieved as compared to the conventional means reported in the literature, particularly with regards to the classification of skateboarding tricks. The encouraging results reported suggests that the proposed pipeline could be beneficial in providing an objective-based judgment in The findings of the present investigation are in agreement with other studies that have employed such a technique in different applications, for instance, Lee, Yoon and Cho (2017) , Rangasamy et al (2020) as well as Mahendra Kumar et al (2021) . Nonetheless, it is worth noting that the efficacy of the pipelines is highly dependent on the dataset utilized, and the performance may vary.…”
Section: Resultssupporting
confidence: 91%
“…This study exploits the use of three families of pre-trained CNN models, i.e ., the MobileNet, NasNet and ResNet families. The rationale of employing transfer learning (TL) models is to reduce the model development time as the CNN models are not required to be built from scratch ( Amanpour & Erfanian, 2013 ; Chronopoulou, Baziotis & Potamianos, 2019 ; Mahendra Kumar et al, 2021 ). A departure from conventional means of using such models is that the present study replaces the fully connected layers that is often referred to dense layers with a conventional machine learning model, i.e ., SVM.…”
Section: Methodsmentioning
confidence: 99%
“…Then, when growing a tree, only a random subset of all attributes is considered at each node, calculating the best split for that subset instead of always calculating the best possible split for each node. Thus, simplifying the optimization procedure, random trees use this split selection to create a reasonably balanced tree where a single global setting for the ridge value works across all leaves [26].…”
Section: Classification Algorithmsmentioning
confidence: 99%
“…We selected the Morlet mother wavelet for this purpose, as it has been extensively used in biomedical signal processing. [17,27,28] We set the frequency limits to range between 0.5 and 100 Hz. The resulting scalograms were concatenated along their horizontal axis and saved as normalized grayscale images.…”
Section: Continuous Wavelet Transformmentioning
confidence: 99%